Project-based learning on pascal’s law: A quasi-experimental study on problem-solving skills in environmental contexts - Sri Hartini; Dewi Dewantara; Arina Meilani (Education and Development Research, 2026)
This study examined the effectiveness of a project-based learning (PjBL) module on Pascal’s Law in improving students’ problem-solving skills within environmental contexts. The research employed a non-equivalent control group pretest–posttest design involving two classes of grade XI students at a senior high school in Barito Kuala district. The study groups consisted of a control class (n=21) and an experimental class (n=22). Data were obtained through learning outcome tests and analyzed using normality and homogeneity tests, Mann-Whitney U test, and effect size calculation. The findings reveal that the PjBL module significantly enhanced students’ problem-solving abilities. The most substantial improvements were observed in fact-finding and solution-finding, while moderate progress was identified in objective finding, problem finding, idea finding, and acceptance finding. The effect size reached 0.72 (medium). These findings indicate that the the PjBL module on Pascal’s Law is effective in strengthening problem-solving skill while also fostering environmental awareness and higher-order thinking. The module thus provides an alternative learning resource to support contextual and skill-oriented physics education.